The Nurse Plant Acacia spirorbis Enriches Ectomycorrhizal Community Composition of a Target Species: Tristaniopsis calobuxus - Anne Houlès; Karine Gotty; François Joussemet; Bryan Vincent; Laure Hannibal; Magali Patrois; Philippe Jourand; Marc Ducousso (Diversity, 2022)
We investigated the suitability of Acacia spirorbis Labill., a tropical ectomycorrhizal (ECM) tree, as a nurse plant to improve the growth of Tristaniopsis calobuxus Brongn. & Gris seedlings for the restoration of nickel mines in New Caledonia. Rehabilitation of nickel mines in New Caledonia is a major concern. In such harsh soil conditions, ectomycorrhizal (ECM) symbiosis is important for tree growth, survival, and resistance. To improve ecological restoration in New Caledonia, new technical itineraries have undergone experimentation using ECM as a plant nurse, allowing ECM saplings to rapidly acquire a wide range of ECM fungi. We transplanted ECM seedlings of Tristaniopsis calobuxus from the nursery to bare ferralitic soils harbouring some scattered 12-year-old Acacia spirorbis to be used as ECM nurse plants. Using molecular characterisation of ITS rDNA, we characterised ECM fungal communities of A. spirorbis and of T. calobuxus saplings at transplanting time and 13 months later. We observed changes in the composition of fungal communities of T. calobuxus with an increase in diversity, notably the appearance of operational taxonomic units (OTUs) affiliated with /russula, /boletus and /pisolithus-scleroderma and a decrease in ubiquitous nursery order such as /sebacina. We also observed a higher number of shared OTUs between T. calobuxus and A. spirorbis. The vicinity of A. spirorbis enabled diversification and adaptation of the T. calobuxus ECM fungal community. These results led us to recommend A. spirorbis as a good nurse tree candidate in the framework of ecological restoration of mine sites.